Resilience and functional capacity in the elderly - Couto, Fernanda Bueno D`Elboux (2010)
The aging process has been the main subject of several studies, due to the increasing number of elderly in the world population, the expenses from chronic diseases or the ever-growing number of active elderly. Fact is, the elderly are often highlighted in surveys, showing aspects not formerly questioned. To discuss functional independency in aging seems commonplace, but the interaction between psychological aspects as self-efficacy, self-esteem and resilience, has been subject to studies. The intent of this paper is to present concepts referring to the functional capacity in the elderly and correlate those to the psychological aspects, mostly to the concept of resilience. Finally, we propose the concept of physical-functional resilience.